Given the equation.

x + y= xy

We need to find dy/dx

We will use implicit differentiation.

==> (x+y)' = (xy)'

==> x' + y' = (x)y' + x'(y)

==> 1 + y' = xy' + y

Now we will combine terms with y' on the left side.

==> y' - xy' = y-1

==> y'(1-x)= y-1

==> y'= (y-1)/(1-x)

**==> dy/dx = (y-1)/(1-x)**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now